SEKOLAH HEBAT TANPA NARKOBA: GERAKAN EDUKASI UNTUK MELINDUNGI GENERASI MUDA GEN-Z - Wahyuni Wahyuni; Rahmat Muliadi; Aprilia Aprilia; Fauziyah Oktaviana; Muhammad Alim; Shinta Sartika; Wd. Inayah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The abuse of narcotics, psychotropic substances, and other addictive substances (NAPZA) is a major issue that threatens the health, social development, and future of the younger generation, particularly Generation Z. Limited education and strong environmental influences are key factors that increase the risk of drug abuse among adolescents. This community service program aimed to improve students' knowledge, awareness, and preventive attitudes toward the dangers of NAPZA abuse through an educational intervention conducted in a school setting. The program was implemented at SMA Negeri 2 Kendari, involving 30 students as participants in collaboration with the National Narcotics Agency (BNN) of Kendari City. The educational methods included interactive lectures, group discussions, question-and-answer sessions, and the delivery of educational materials through presentations and leaflets. The topics covered included the types of NAPZA, their health impacts, social and legal consequences, and strategies for preventing drug abuse. The results demonstrated that participants actively engaged in the activities, participated enthusiastically in discussions, and showed improved understanding of the dangers of drug abuse and the importance of protecting themselves from negative environmental influences. Furthermore, the program successfully fostered students' awareness and confidence to refuse drug-related invitations, report suspected cases of drug abuse, and serve as peer educators within their school community. In conclusion, this community service program was effective in enhancing students' knowledge and awareness regarding the dangers of NAPZA and contributed to the creation of a healthy, safe, and drug-free school environment through collaboration among higher education institutions, schools, and the National Narcotics Agency